Local Open Government Issues In Kaduna State, Nigeria - Afandi, Syed Agung; Erdayani, Rizki; Afandi, Muslim (Jurnal Pallangga Praja (JPP), 2025)
This study aims to analyze key issues of open government in Kaduna State. Kaduna State plays a major role in Nigeria as the only local government pilot program of the Open Government Partnership. A qualitative approach and bibliometric analysis method were used in this study. The research data were obtained from the official website of the Kaduna State Government and sourced from the Google Scholar database. The findings of this study indicate that the study of open government in Kaduna State is not popular. The topics that dominate the study of open government in Kaduna State are farming, education, transparency, health, conflict, information resources, and information and communication technology. Meanwhile, the current and potential topics in the study of open government in Kaduna State include cybersecurity, e-government systems, health insurance, food security, electoral systems, democratic governance, and independent electoral commissions. Kaduna State is currently focusing on five main commitments, namely strengthening the participatory budget process, the Open Contracting Data Standard and Open Contracting 4 Infrastructure Data Standard, access to information for citizen engagement, strengthening social protection systems, and improving service delivery in education and health sectors. These commitments have the potential to create a more open government in Kaduna State.